2017
DOI: 10.1186/s12863-017-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

Circadian CLOCK gene polymorphisms in relation to sleep patterns and obesity in African Americans: findings from the Jackson heart study

Abstract: BackgroundCircadian rhythms regulate key biological processes and the dysregulation of the intrinsic clock mechanism affects sleep patterns and obesity onset. The CLOCK (circadian locomotor output cycles protein kaput) gene encodes a core transcription factor of the molecular circadian clock influencing diverse metabolic pathways, including glucose and lipid homeostasis. The primary objective of this study was to evaluate the associations between CLOCK single nucleotide polymorphisms (SNPs) and body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Recently, Riestra et al. (2017) found that among African‐Americans, the T‐allele carriers of the SNPs rs2070062 and rs6853192 had significantly shorter sleep duration. Given that these SNPs of the CLOCK gene can contribute to sleep problems, more modern methods should be encouraged to genotype the entire CLOCK gene in order to obtain thorough results in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Riestra et al. (2017) found that among African‐Americans, the T‐allele carriers of the SNPs rs2070062 and rs6853192 had significantly shorter sleep duration. Given that these SNPs of the CLOCK gene can contribute to sleep problems, more modern methods should be encouraged to genotype the entire CLOCK gene in order to obtain thorough results in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A SNP (rs17601612) in the dopamine D2 receptor gene was significantly associated with sleep duration in European subjects, but with an opposite direction of association in AAs ( 69 ). In AA participants in the Jackson Heart Study, genetic analysis found that a SNP in the CLOCK (circadian locomotor output cycles protein kaput) gene, which is important to circadian metabolic pathway regulation, was correlated with short sleep duration and BMI ( 70 ).…”
Section: Part 3: Disparities In Sleep and Cardiometabolic Health In Amentioning
confidence: 99%
“…CLOCK is a transcription factor and one of the primary regulators of the transcription of the circadian clock gene. It is also the regulator of expression of the various transcription factors required for control of the diverse physiological and behavioral processes that occur in a circadian fashion [58]. In this study, rs11932595 SNP of the CLOCK gene was connected with systolic blood pressure in MI patients.…”
Section: Discussionmentioning
confidence: 60%